2004
DOI: 10.1007/s00262-004-0534-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IAP family proteins in colon cancers from patients with different age groups

Abstract: Members of the inhibitor of apoptosis protein (IAP) family including survivin, are expressed in many tumors. However, age-related changes in their expression in cancer have not been clarified. Thus, we investigated the expression of mRNA-coding for IAP family proteins in colon cancer samples from young (<70 years of age) and elderly (>70 years) patients by real-time quantitative RT-PCR. Samples were collected from cases with well-differentiated adenocarcinoma or moderately differentiated adenocarcinoma and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 21 publications
8
40
1
Order By: Relevance
“…Chemoresistance results from a variety of complicated factors, including mutations in specific drug targets, impaired drug transporters, DNA repair activation, increased drug efflux and evasion of apoptosis by cancer cells (37,38). Among these mechanisms, evasion of apoptosis is considered a major cause of drug resistance since many chemotherapeutic agents act through the induction of apoptosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…Chemoresistance results from a variety of complicated factors, including mutations in specific drug targets, impaired drug transporters, DNA repair activation, increased drug efflux and evasion of apoptosis by cancer cells (37,38). Among these mechanisms, evasion of apoptosis is considered a major cause of drug resistance since many chemotherapeutic agents act through the induction of apoptosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study (Endo et al, 2004) found that NAIP mRNA expression was decreased in well and moderately differentiated colon adenocarcinoma, compared with adjacent BM-derived macrophage culture BM was flushed from the tibia and femur, red blood cells were lysed, and cells were cultured in BMDM medium (DMEM, 10% FCS, 20% supernatant from L929 cell-conditioned medium, 1% Penicillin-Streptomycin (10 000 U/ml; Invitrogen) in 10 cm culture Petri dishes for 6-7 d. Adherent cells were lifted from the Petri dish using Accutase (Invitrogen).…”
Section: Models Of Crc and Colitismentioning
confidence: 91%
“…Subsequently, it induces DNA damage recognition proteins to signal to downstream effectors such as p53, resulting in cell cycle arrest and apoptosis. To date, little is know on the Livin expression profile in CRC except for preliminary reports [17][18][19][20][21]. Neither is it known about the relationship between Livin expression and cisplatin sensitivity in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports helped to expand its expression profile to variant tumors such as melanoma, leukemias, bladder, breast, cervical, nasopharyngeal and lung cancer [5][6][7][8]. However, there are only limited reports regarding its expression in CRC except some preliminary studies [17][18][19][20][21]. Previously, Livin expression was described in only 3 colon cancer cell lines (LoVo, Previous reports demonstrated that Livin contributed to resistance to fluorouracil, etoposide, and vincristine for tumor cells, but no studies were intended to explore the relationship between Livin expression and resistance to platinum.…”
mentioning
confidence: 99%